Attachment in Supervision: Using a Relational Lens to Understand Supervisory Dynamics - Salam Soliman (Psychotherapy and Counselling Journal of Australia)
This article aims to introduce a relational model of supervision based on attachment theory using the Circle of Security as a model for understanding supervisory dynamics. The article briefly reviews attachment theory and the historical context of clinical supervision and provides a brief discussion regarding the importance of ongoing supervision as a way to support frontline staff and mitigate the impact of secondary traumatic stress and burnout. Applying concepts from reflective supervision and attachment theory, the article introduces the Supervisor's Circle of Security and presents a matrix model of supervisor—supervisee relationships, lending 16 possible attachment combinations for the dyad. Potential presentations of each of the dyadic compositions is discussed followed by clinical vignettes.